2015
DOI: 10.1158/2326-6066.cir-14-0018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD39 Enzymatic Function at the Surface of Tumor Cells Alleviates Their Immunosuppressive Activity

Abstract: The ectonucleotidases CD39 and CD73 hydrolyze extracellular adenosine triphosphate (ATP) and adenosine diphosphate (ADP) to generate adenosine, which binds to adenosine receptors and inhibits T-cell and natural killer (NK)-cell responses, thereby suppressing the immune system. The generation of adenosine via the CD39/CD73 pathway is recognized as a major mechanism of regulatory T cell (Treg) inhibited the proliferation of CD4 and CD8 T cells and the generation of cytotoxic effector CD8 T cells (CTL) in a CD39… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
164
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 49 publications
16
164
1
Order By: Relevance
“…By measuring either extracellular ATP degradation or the release of free phosphate in cell culture supernatants, we demonstrated that all CD39-expressing cells display strong ATPase activity that is counteracted by the chemical CD39 inhibitors ARL 67156 and POM-1. 7 As previously described for ovarian tumor cells, 6 we found that some cancer cell lines also express CD73, suggesting that tumor cells co-expressing CD39 and CD73 may exert potent immunosuppressive actions via adenosine. Supporting this hypothesis, we demonstrated that the degradation of ATP into AMP and adenosine by the SK-MEL-5 melanoma cell line is associated with the suppression of CD4 C and CD8 C T-cell proliferation as well as the generation of cytotoxic effector CD8 C T cells.…”
Section: Introductionsupporting
confidence: 76%
“…By measuring either extracellular ATP degradation or the release of free phosphate in cell culture supernatants, we demonstrated that all CD39-expressing cells display strong ATPase activity that is counteracted by the chemical CD39 inhibitors ARL 67156 and POM-1. 7 As previously described for ovarian tumor cells, 6 we found that some cancer cell lines also express CD73, suggesting that tumor cells co-expressing CD39 and CD73 may exert potent immunosuppressive actions via adenosine. Supporting this hypothesis, we demonstrated that the degradation of ATP into AMP and adenosine by the SK-MEL-5 melanoma cell line is associated with the suppression of CD4 C and CD8 C T-cell proliferation as well as the generation of cytotoxic effector CD8 C T cells.…”
Section: Introductionsupporting
confidence: 76%
“…31,36 CD39 belongs to the arsenal of regulatory T cells and ovarian cancer cells to generate an immunosuppressive environment. 43,46,59 Here, we describe that ovarian tumor-infiltrating macrophages are also active players of this process. Newly recruited monocytes in the tumor are in contact with ATPderived nucleotides which may participate to the acquisition of an IL-10 high IL-12 low immunosuppressive phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…The field of cancer immunology has recently been fed with studies on the roles of the ectonucleotidases CD39 and CD73 on the biology of tumor-associated immune cells, showing that CD39 and/or adenosine receptors are major negative regulators of T cells, myeloid cells and cancer cells that could be targeted within the tumor microenvironment. 20,21,43 To support our choice to target CD39, it has been shown that CD73 (an ectonucleotidase hydrolyzing AMP into Adenosine) may be dispensable for M2-type macrophage polarization. 61 Numerous studies have underlined the role of IL-27 in the generation of an immunoregulatory microenvironment in physiological and pathological settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations